The dynamic epigenetic atlas and its effects on instability of starch and seed storage protein quality traits in wheat (Triticum aestivum L.) - Wang, Yaping; Miao, Lingfeng; Wu, Haibin; Duan, Xiaoliang; Chang, Liu; Hong, Yu; Guo, Weilong; Sun, Hui (Frontiers in Plant Science, 2025)
Environmental factors significantly influence wheat grain quality by modulating starch biosynthesis and seed storage protein (SSP) composition, yet the underlying epigenetic mechanisms remain elusive. Here, we performed an integrated multi-omics analysis on the wheat cultivar ‘Fengdecunmai 5’ cultivated in two contrasting environments using WGBS, ChIP-seq (H3K27ac/H3K27me3), and RNA-seq. Epigenomic profiling revealed that environmental variation triggers extensive epigenetic reprogramming, with changes in H3K27ac enrichment being a primary epigenetic signature associated with the transcriptional divergence of starch and SSP biosynthesis genes during early development. Reconstruction of the transcriptional regulatory networks (TRNs) identified 86 essential transcription factors (TFs) that regulate 9,250 target genes in response to environmental impact. Our findings provide novel insights into the molecular basis of wheat quality instability across environments from an epigenetic perspective and highlight the critical role of histone modifications in regulating wheat seed quality.